2020
DOI: 10.1111/ecog.04868
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds in seascape connectivity: the spatial arrangement of nursery habitats structure fish communities on nearby reefs

Abstract: Ecosystems are linked by the movement of organisms across habitat boundaries and the arrangement of habitat patches can affect species abundance and composition. In tropical seascapes many coral reef fishes settle in adjacent habitats and undergo ontogenetic habitat shifts to coral reefs as they grow. Few studies have attempted to measure at what distances from nursery habitats these fish migrations (connectivity) cease to exist and how the abundance, biomass and proportion of nursery species change on coral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 72 publications
0
37
0
1
Order By: Relevance
“…Besides the gaps in habitat, other studies have found that at scales <1000 km the larval dispersal and recruitment were the main processes affecting genetic structure (Berkström et al, 2020;Dalongeville et al, 2018;Pascual et al, 2017;Schunter et al, 2019).…”
Section: Genetic Structure At Local Scalesmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides the gaps in habitat, other studies have found that at scales <1000 km the larval dispersal and recruitment were the main processes affecting genetic structure (Berkström et al, 2020;Dalongeville et al, 2018;Pascual et al, 2017;Schunter et al, 2019).…”
Section: Genetic Structure At Local Scalesmentioning
confidence: 99%
“…These include habitat discontinuities (Blanco‐Gonzalez et al ., 2016; Sandoval‐Huerta et al ., 2019; Torquato et al ., 2019) and strong environmental gradients (García‐De León et al ., 2018; Sandoval‐Huerta et al ., 2019). In addition, the life cycle of each species, including the breeding season, dispersal ability (Frisk et al ., 2012; Treml et al ., 2012) and the location of the habitats for juveniles and adults, plays an important role in population demography, connectivity and the location of those genetic breaks (Berkström et al ., 2020; Blanco‐Gonzalez et al ., 2016; Pascual et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations